2015
DOI: 10.1002/2014wr016258
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the effects of excess rainfall properties on the scaling structure of peak discharges: Insights from a mesoscale river basin

Abstract: Key theoretical and empirical results from the past two decades have established that peak discharges resulting from a single rainfall-runoff event in a nested watershed exhibit a power law, or scaling, relation to drainage area and that the parameters of the power law relation, henceforth referred to as the flood scaling exponent and intercept, change from event to event. To date, only two studies have been conducted using empirical data, both using data from the 21 km 2 Goodwin Creek Experimental Watershed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 59 publications
6
58
0
Order By: Relevance
“…Due primarily to the spatial and temporal variability of rainfall, defining a rainfall-runoff event for a mesoscale basin such as the Iowa River basin is not a straightforward task. Ayalew et al (2015) analyzed streamflow data from the basin for the 12-year period from 2002 to 2013. They showed that a scale invariant peak-discharge spatial organization emerges when the entire basin gets a runoff generating rainfall event at some point during a time window that is equivalent to the basin's concentration time, which is the time required for a parcel of water to travel from the most remote hillslope in the basin to the outlet.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Due primarily to the spatial and temporal variability of rainfall, defining a rainfall-runoff event for a mesoscale basin such as the Iowa River basin is not a straightforward task. Ayalew et al (2015) analyzed streamflow data from the basin for the 12-year period from 2002 to 2013. They showed that a scale invariant peak-discharge spatial organization emerges when the entire basin gets a runoff generating rainfall event at some point during a time window that is equivalent to the basin's concentration time, which is the time required for a parcel of water to travel from the most remote hillslope in the basin to the outlet.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration time is about 15 days for the Iowa River basin. The criteria Ayalew et al (2015) used to define peak discharge events are briefly summarized as follows. First, they determined whether a single peaked hydrograph is observed at the outlet and noted the time when the peak discharge occurred.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations